(3OeL GdCTNGU Phj GdEYGbI aj GdLgGR GdEOGQj ddOhdI (B((3OQGSI ebGQfI HGdbGfhf GdeUQj hGdchjJj(B)/s - (3eHGQc HOGM eMeO GdHOGMs; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQI(B.s (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B- (3LGeYI GdbGgQI,s, 2025)
(3jcef GdOGaY GdCSGSj hQGA gPG GdHMK aj GdVQhQI GdedMI dOeL GdCTNGU Phj GdEYGbI Vef GdLgGR GdEOGQj ddOhdI, EP dG jecf JMbjb JfejI MbjbjI hTGedI aj Xd JZjjH TQjMI ef echfGJ GdHfjI GdHTQjI dPdc GdeLJeY, hGYJeOJ GdOQGSI Ydi GdefgL GdhUaj GdJMdjdj HgOa HfGA JUhQ Ydej efVHW jQJcR Ydi GdCSS GdfXQjI ef LgI, hjQJHW HGdJWHjbGJ GdYedjI ef LgI CNQi, hHjfJ fJGFL GdOQGSI hLhO GdJRGe JTQjYj hGVM aj GdchjJ heUQ fMh OYe hJecjf Phj GdEYGbI, hCcOJ GdOQGSI Ydi CgejI GdJOGHjQ GdEjLGHjI, eKd JNUjU fSH JhXja EdRGejI, cGdjI dJMbjb GdYOGdI GdGLJeGYjI hJYhjV GdEbUGA GdJGQjNj, hChUJ GdOQGSI HVQhQI JYOjd GdJTQjYGJ dQaY fSHI JhXja Phj GdEYGbI, hEWdGb HQGeL eSJeQI dJOQjHge hJCgjdge HeG jJfGSH eY GMJjGLGJ Shb GdYed(B.s
(3QSGFd fSNI efaQOIs
(3JMJhj Ydj UaMI YfhGf hedNU HGddZI GdEfLdjRjIs
(3CWQhMI (B((3OcJhQGI(B)- (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdYGe, (B2025.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdEOGQjs; (3GdbGfhf GdYGes; (3GdOeLs; (3GdCTNGU Phj GdEYGbIs; (3GdLgGR GdEOGQj ddOhdIs; (3GdbGfhf GdchjJjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdEOGQjs